Measuring Customer Based-Brand Equity Empirical Evidence from Fast Food Brands in Northern Cyprus - Sadatrad, Mahta (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2013)
This study pursues to examine the practicality and applications of a customer-based brand equity model in the North-Cyprus fast-food market. This research is based on design, methodology, and approach most common conceptual framework of brand equity. The study is demonstrated which is a significant relationship between five dimensions of own study that dimensions individually are related to each other. In the decade, brand equity components are challenging issues. Because of this, the aim of my thesis is to investigate the effects of brand equity components (brand awareness, brand image, brand quality, brand value and brand loyalty) on brand equity itself. This study is used to measure fast-food usage of 200 university students and their senses. The purpose of my study is suggested the high quality of brand equity to the managers for being update and finding their costumers’ needs. This study also provides insights about the understanding of North-Cyprus fast-food market consumers’ perceptions of overall brand equity and its dimensions. Keywords: Brand Equity, Customer-based Brand Equity (CBBE), Brand Awareness, Brand Loyalty, Brand Image, Brand Value, Northern Cyprus

ÖZ: Bu çalışmanın temel amacı müşteri tabanlı marka değeri modelinin hızlı-yiyecek (fast-food) sektöründe incelenmesi ve Kuzey Kıbrıs Türk Cumhuriyeti’nde uygulamasını yapmaktır. Araştırmanın temeli marka değeri kavramsal modelini, tasarımı olmuştur. Çalışmamız marka değeri modelindeki beş boyutu incelemiş ve aralarında anlamlı ilişki olduğunu tesbit etmiştir. So on yılda, marka değeri çalışmaları artmış ve zorlaşmıştır. Bu nedenle, çalışmanın amacı marka değer boyutlarının etkilerini incelemek olmuştur (marka farkındalığı, marka imajı, marka kalitesi, marka değeri ve marka bağımlılığı). Çalışmanın örneğini 200 üniversite öğrencisi teşkil etmektedir. Çalışma Kuzey Kıbrıs Türk Cumhuriyetin’deki hızlı-yiyecek (fast-food) sektörü müşterilerini incelemiş ve bu müşterilerin toplam marka değeri ve boyutlarını nasıl algıladıklarını saptamıştır.
Master of Arts in Marketing Management. Thesis (M.A.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Business Administration, 2013. Supervisor: Assoc. Prof. Dr. Mustafa Tümer.
Keywords: Business Administration; Marketing Management; Brand name products - Fast-Food - Marketing - Cyprus, North; Brand Equity; Customer-based Brand Equity (CBBE); Brand Awareness; Brand Loyalty; Brand Image; Brand Value; Northern Cyprus